CATALYST DEVELOPMENT AND PRODUCTION TECHNOLOGY OF BIO-BTX FROM EMPTY PALM BUNCHES - Citrawijaya, Andre
Benzene, toluene, and xylene (BTX) demand are very high due to their various application. This high demand is increasing by time. So far, BTX is still produced from crude oil and fossil resources. However, the declining petroleum oil resources is threatening the sustainability of BTX production. Therefore, other methods for producing BTX are important to be studied. Oil palm tree, as one of Indonesia’s largest commodity, produces waste in the form of empty fruit bunch (EFB). EFB has a high potential to be used as alternative resources for producing BTX. The purpose of this research is to develop a catalyst which can be used for conversion of phenolics compunds derived from lignin depolymerization to produce BTX through a hydrodeoxygenation process, which is integrated with dehydrogenation of methylcyclohexane. Methylcyclohexane functions as a hydrogen donor for the hydrodeoxygenation of phenolic compounds. There are several stages in this research, including material preparation, catalyst modification, catalyst characterization, main experiments, and product analysis. The main ingredients for this research are guaiacol and methylcyclohexane. The catalyst for this research is Ni-Mo/HBeta. Catalyst activity test is carried out in hydrothermal batch reactor, at 265oC, 20 bar N2, mass ratio of catalyst to feed 1:10, for 4 hours. Studied catalysts are HBeta, 3Ni-12Mo/HBeta, 7Ni-8Mo/HBeta, and 12Ni-3Mo/HBeta. Liquid product is analyzed by using GC-MS. The data is interpreted by classifying aromatic compounds based on number of oxygen, methyl, methoxyl, and hydroxyl. The purpose are to find the deoxygenation activity, methylation, demethoxylation, and dehydroxylation of each catalyst used. Catalyst which produce toluena from Guaiacol HDO integrated with MCH dehydrogenation is HBeta. Meanwhile, Ni-Mo/HBeta catalysts are unable to product BTX due to low dehydroxylation activity, high methylation activity, and decreased concentration of Brønsted acid sites caused by impregnation.